Case report: Cerebrotendinous xanthomatosis treatment follow-up - Ejsmont-Sowała, Karolina; Książek, Tomasz; Maciorowska-Rosłan, Katarzyna; Rosłan, Joanna; Czarnowska, Agata; Jakubiuk-Tomaszuk, Anna; Tarasiuk, Joanna; Kapica-Topczewska, Katarzyna; Kułakowska, Alina (Frontiers in Neurology, 2024)
Xanthomatosis is a genetic disease inherited in an autosomal recessive manner. The specific phenotypic features are associated with patient's genetic profile. The result of the mutation is disorder of cholesterol synthesis and the accumulation of its precursors in tissues. The characteristic symptoms are progressive cerebellar ataxia, cataract, diarrhea, and the deposition of cholesterol in the tendons. Our objective is to follow-up information to treatment efficacy of 22-year-old patient diagnosed with cerebrotendinous xanthomatosis through 1.5 year observation.In 2012, an 11-year-old patient with a long history of deformed feet and frequent yellowing of the skin, was admitted to the Department of Neurology due to seizures. In 2013, the patient began to suffer from diarrhea, and its frequency was correlated with the concentration of bilirubin in the blood. In the same year cataract was diagnosed. Gradually, the patient starts to complain about progressive difficulties in moving. In 2019, genetic tests confirmed the diagnosis of cerebrotendinous xanthomatosis. Since July 2021, the patient has been treated with chenodeoxycholic acid. The deterioration of patient's mobility has been significantly inhibited, consequently his quality of life has improved.The presented case report underscores the efficacy of CDCA supplementation in halting the progression of CTX, resulting in marked improvements in the patient's quality of life.